'Not my child': parenting, pornography, and views on education. Issue 4 (2nd October 2021) - Davis, A. C.; Wright, C.; Curtis, M.; Hellard, M. E.; Lim, M. S. C.; Temple-Smith, M. J.
ABSTRACT: Most young people will be exposed to online pornography for the first time during childhood or early adolescence. Despite limited evidence of long term impacts, concerns about the negative influence of pornography on young viewers' sexual attitudes and practices have led to calls for the development of policy, resources, and guidelines to assist in navigating these experiences in family and community settings. Pornography and sex education are clearly sensitive topics and there is a need for research examining parents' perceptions of this highly complex issue to inform evidence-based education and social policy. We conducted a qualitative study using in-depth interviews, with parents ( n  = 20) of 10–16-year-old children. Parents were recruited on a spectrum of demographic, educational, and cultural backgrounds from across the greater region of Melbourne, Australia. Findings revealed that parents perceptions of their children, their own experiences of pornography use and internet communications technology, as well as a lack of involvement in school-based sex education, affected their ability to respond to the issue. Most parents preferred open dialogue with their own child over household level filters or regulation of online exposure. The study provides new considerations to inform policy responses and education program design.